Development of STEM-Based LKPD with Guided Inquiry Design to Improve Student’s Science Process Skills (Radiasi : Jurnal Berkala Pendidikan Fisika, 2022)
This study aims to develop a STEM-based Student Worksheet (LKPD) through Guided Inquiry to Improve Students' Science Process Skills. This research and development method refers to the Borg & Gall model up to the 8th stage, namely a trial use that has been adapted to research needs, namely developing LKPD and seeing an increase in students’ science process skills after using LKPD in learning activities, with research subjects in class XI IPA 5 and XI. IPA 3, each totaling 24 students. The results obtained are: 1) the validation of the LKPD that has been developed is "very valid" with the percentage of material experts at 82.36% and the percentage of media experts being 82.44%; 2) the feasibility of the developed LKPD is very feasible with a percentage of 95.43%; 3) The LKPD developed is declared practical because the response questionnaires from students are categorized as practical 4) the results of students' responses to the use of "very good" trials with a percentage of 87.33%; 5) The effectiveness of LKPD is seen from the achievement of students' science process skills with an N-Gain value of 0.78 or with a percentage of 78% overall very good and increasing in every meeting. It was concluded that the development of STEM-based LKPD through Guided Inquiry was valid and feasible and could be used in the Physics learning process to improve Students' Science Process Skills on Thermodynamic Materials.
Keywords: LKPD; STEM; Guided inquiry; Science process